Begomovirus Infection Patterns in Melons of Indonesian Lowlands: Growth Trends Among Ecosystems and Genotypes - Hadi, Rizko; Hartono, Sedyo; Daryono, Budi Setiadi (HAYATI Journal of Biosciences, 2024)
Melon plants are challenged with diseases caused by begomovirus. To understand the epidemiology, ecology, and evolution of this genus, information about its temporal and spatial patterns of infection in specific ecosystems is needed. This paper aimed to report begomovirus infections in melon plants cultivated in greenhouse ecosystems under local climactic conditions in the Indonesian lowlands. To achieve this goal, we determined the begomovirus infection rates, plant physiological characteristics, and whitefly number. The data obtained were then analyzed using analysis of variance (ANOVA) and Pearson’s correlation. We documented the symptoms of begomovirus infection in melon plants cultivated in Indonesian lowlands. We also documented begomovirus infections in melon plants, which increased from the first exposure to after the reproductive phase. In different artificial ecosystems, we explained differential patterns of begomovirus infections in melon plants. Finally, we captured the variation in infection conditions found among melon host genotypes.